2018
DOI: 10.1186/s12864-018-5284-7
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiome variances in sample groups categorized by clinical criteria of bacterial vaginosis

Abstract: BackgroundOne of the most common and recurrent vaginal infections is bacterial vaginosis (BV). The diagnosis is based on changes to the “normal” vaginal microbiome; however, the normal microbiome appears to differ according to reproductive status and ethnicity, and even among individuals within these groups. The Amsel criteria and Nugent score test are widely used for diagnosing BV; however, these tests are based on different criteria, and so may indicate distinct changes in the vaginal microbial community. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 49 publications
6
29
0
3
Order By: Relevance
“…The results revealed that women with BV have a heterogeneous VMB that is not dominated by a single taxon and no species is universally present in all of BV-positive women (Srinivasan et al, 2012 ). It is supported by the findings of Chen et al ( 2018 ) that significant differences in the bacterial composition of the BV microbiome were observed among BV groups defined by Amsel's criteria or Nugent scoring.…”
Section: Factors Complicating the Diagnosis Of Bvsupporting
confidence: 65%
See 1 more Smart Citation
“…The results revealed that women with BV have a heterogeneous VMB that is not dominated by a single taxon and no species is universally present in all of BV-positive women (Srinivasan et al, 2012 ). It is supported by the findings of Chen et al ( 2018 ) that significant differences in the bacterial composition of the BV microbiome were observed among BV groups defined by Amsel's criteria or Nugent scoring.…”
Section: Factors Complicating the Diagnosis Of Bvsupporting
confidence: 65%
“…Despite multiple molecular and genomic studies being conducted at species or microbiome level, there is no consensus on the group of bacterial species that may directly cause BV (Fethers et al, 2012 ; Srinivasan et al, 2012 ; Chen et al, 2018 ; Muzny et al, 2018 ). Srinivasan et al ( 2012 ) performed broad-range 16S ribosomal RNA (rRNA) gene PCR and pyrosequencing to describe the composition and diversity of the VMB in women with BV, diagnosed either by Amsel's criteria or Nugent scoring.…”
Section: Factors Complicating the Diagnosis Of Bvmentioning
confidence: 99%
“…The clinical diagnosis of highly common BV and other vaginal infections relies strongly on the microscopic examination of vaginal smears or visual assessment of the vaginal discharge. The correspondence between the microscopic findings and molecular VMB analysis has been previously studied using Nugent score as a reference method 22,28,29 . Here we expand these studies by comparing the light microscopy findings of the Pap smears to VMB composition determined with 16S rRNA amplicon sequencing in asymptomatic women.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse community state type (CST4) identified by community sequencing is strongly associated with bacterial vaginosis (BV), but CST4 does not always correlate to BV diagnosed by microscopy and symptoms . Community sequencing is being used to identify relationships between specific bacterial taxa and symptomatic BV, and to more precisely elucidate the role of the vaginal microbiome in preterm birth (PTB) and sexually transmitted infections (STI) . There appears to be growing agreement that low levels of L. crispatus and a diverse vaginal microbiome (CST4) are associated with higher PTB risk in some, but not all, populations of pregnant women.…”
Section: Research In the Vaginal Microbiome Using Community Sequencingmentioning
confidence: 99%